Cross Country Comparison of Regional Mechanisms for Delivery of Free Legal Assistance - World Bank (Washington, DC, 2014)
This report provides comparative analysis of different delivery models of Free Legal Aid (FLA) in Montenegro, Bosnia and Herzegovina (Brcko), Lithuania, Croatia and Slovenia. The field work and data collection was conducted from November to December 2013. The survey was funded by the Multi Donor Trust Fund for justice sector support, established with generous contributions from the European Union (EU) delegation in Serbia, United Kingdom Department for International Development, the Swedish International Development Cooperation Agency, Norway, Denmark, the Netherlands, Slovenia, Spain, and Switzerland.